Lifestyle as a cultural force in brand phenomena: analysing Red Bull Portugal - Delgado, Beatriz Maria Soares (My University, 2023)
This dissertation presents a comprehensive analysis towards lifestyle brands, with a specific focus on the case study of Red Bull. Lifestyle brands have become increasingly influential in shaping consumer preferences and behaviors, as they offer products and experiences that align with consumers' values, aspirations, and self-identities. Understanding how consumers perceive and engage with lifestyle brands is essential for marketers to develop effective strategies and build strong brand-consumer relationships. The research employs a mixed-methods approach, combining qualitative data collection methods, such as interviews (Desai, 2002), participant observation (Kawulich, 2005), in depth analysis using Kapferer Identity Prism (Kapferer, 2015) that provide in-depth insights into consumers' perceptions, attitudes, and emotional connections with Red Bull as a lifestyle brand. In addition, a secondary data analysis (Vartanian, 2011) was conducted to gain insights into how Red Bull strategically positions its brand and communicates its message to individuals. Specifically focuses on Red Bull Portugal, this study examines various aspects of consumer reception, including brand image, brand personality, consumer identity formation, and brand loyalty. It investigates how Red Bull strategically positions itself as a lifestyle brand and appeals to its target audience through its marketing efforts and brand experiences. Overall, this dissertation contributes to the existing literature on consumer behavior and brand management by providing an in-depth analysis towards lifestyle brands, using Red Bull as a case study. By examining the specific strategies and tactics employed by Red Bull, this research sheds light on the effectiveness of lifestyle branding and provides valuable insights for marketers seeking to navigate the dynamic landscape of consumer preferences and engagement with lifestyle brands.
Keywords: Red Bull; Lifestyle brands; Brand management; Brand personality; Communication